International standards on auditing in the international financial services centres: What matters?. Issue 6 (6th June 2016) - Boolaky, Pran; Omoteso, Kamil
Abstract : Purpose: This paper aims to investigate the position of international financial services centres (IFSCs) in the International Federation of Accountants' countries' status on the adoption of International Standards on Auditing (ISA) and assess the factors influencing ISA adoption in these centres. Design/methodology/approach: This research drew its data from various sources, including the World Economic Forum (WEF) data set, the World Bank Report on Observation of Standards and Codes, the World Development Indicators and the Economic Intelligence Unit Report on Democracy Index on 50 countries classified as IFSCs. The adoption status is then regressed on a number of variables of interest. To establish that the results are robust, the authors used a combination of different regression techniques comprising OLS, multinomial and logistic regressions. Findings: In addition to the gross domestic product growth and education level, this paper adds new evidence to the literature by reporting the positive association between the level of democracy and the enforcement of securities' regulation on ISA adoption. It argues that political, economic, social and legal factors impact on ISA adoption in the IFSCs. Research limitations/implications: The sample size is limited to 50 from a population of 99 IFSCs because of the lack of data. Some of the independent variables are basically archival data. Reliance is placed on WEF with regard to the measurement of protection of minority interest, securities and exchange regulations and on the Economic Intelligence Unit for democracy index. Practical implications: This paper stresses the importance of ISAs in IFSCs and the role of political power and the enforcement of securities laws on the adoption of ISA. Originality/value: This study fills the research gap relating to the absence of empirical studies on ISA adoption and its drivers in IFSCs.